PENERAPAN PENDIDIKAN BERBASIS KEARIFAN LOKAL DI SD NEGERI 8 RAMBUTAN KABUPATEN BANYUASIN MENUJU GLOBAL CITIZEN - Oktarina, Ririn; Ribuwati, Ribuwati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This paper discusses the application of education based on local wisdom in SD Negeri 8 Rambutan, Banyuasin. In the application of local wisdom in SD Negeri 8 Rambutan, Banyuasin there are various materials that will be taught among others on Indonesian language materials that explain the theme of local wisdom that can be taught through material such as fabricating, proverbs or poetry. In addition to other subject matter can also be taught with local themes. Local dance and drama performances presented at the school farewell ceremony are also part of the application of local wisdom-based education in SD Negeri 8 Rambutan, Banyuasin. This article also explains the sources of local wisdom of local culture as well as the objectives of the local wisdom-based education that is nothing other than to realize a dignified Indonesia by applying local wisdom-based education to schools throughout the country. With local wisdom-based education it will explore the various cultures of Indonesia that will ultimately build the insight of environmental sustainability. And local wisdom-based education will also lead to global citizen, which local culture also should be introduced both nationally and internationally so that will create a community with global insight.